2017
DOI: 10.1590/0004-282x20170084
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-brachial index and diabetic neuropathy: study of 225 patients

Abstract: Objective To evaluate neuropathic pain and peripheral vascular disease in diabetics and compare this with the length of time since diagnosis in type 1, and type 2 diabetes. Methods A cross-sectional study with 225 diabetics chosen from their responses on the DN4 questionnaire, who were then evaluated with the ankle-brachial index (ABI), separating type 1 diabetes from type 2 diabetes. Results A higher incidence of neuropathic pain in those over 60 years of age showed an ABI > 1.3. Neuropathic pain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
2
9
1
3
Order By: Relevance
“…3), suggesting an association between cardiorespiratory capacity and exercise tolerance in this population. V O 2max and 6MWD have been reported to be associated in healthy adults and in patients with pulmonary disorders and diseases (12,13,16,53). The present study indicates that V O 2max and 6MWD are associated measures in patients with PAD, which is similar to the findings in healthy adults and patients with pulmonary disorders and diseases.…”
Section: Cardiorespiratory and O 2 Consumption Capacity In The Skeletal Muscle V O 2max Represents Both Cardiorespiratory Capacitysupporting
confidence: 88%
“…3), suggesting an association between cardiorespiratory capacity and exercise tolerance in this population. V O 2max and 6MWD have been reported to be associated in healthy adults and in patients with pulmonary disorders and diseases (12,13,16,53). The present study indicates that V O 2max and 6MWD are associated measures in patients with PAD, which is similar to the findings in healthy adults and patients with pulmonary disorders and diseases.…”
Section: Cardiorespiratory and O 2 Consumption Capacity In The Skeletal Muscle V O 2max Represents Both Cardiorespiratory Capacitysupporting
confidence: 88%
“…Ankle-brachial index (ABI) measurements were taken after a five-minute break with the supine position, which were used to identify the lower extremity arterial disease (LEAD) including hardened vessels and arterial occlusion ( 20 ). The ABI values between 0.9 and 1.3, larger than 1.3 or less than 0.9 were considered as normal and abnormal arterial, respectively ( 21 ). Both diabetic retinopathy and diabetic peripheral neuropathy (DPN) were defined following the American Diabetes Association’s criteria ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite many complaints of DPN symptoms among the subjects, no significant correlation was found in terms of ABI score. In contrast to this result, Chevtchouk et al 19 found a significant difference between normal and abnormal ABI groups (<0.9) with neuropathic pain in people with DM with a duration of >10 years. However, only few subjects in this study had had DM for >10 years.…”
Section: Discussionmentioning
confidence: 63%
“…On the other study, Chevtchouk et al 19 had measured ABI and NDS scores on 126 people with DM and it was found that the sensitivity and specificity of the two scores for predicting DPN were 47% and 90.7%, respectively. NDS is a DPN clinical scoring consisting of vibration perception threshold, perceptions of temperature on the back of the foot, excitatory pain in the big toe, and Achilles reflex examinations.…”
Section: Discussionmentioning
confidence: 99%